Response of the soil hydrothermal environment and cotton yield to different irrigation quotas under biodegradable mulch film in oasis cotton fields: a three-year study - Zhang, Hao; Wang, Dong; Zhang, Xun; Wang, Yifan; Liu, Haijun; Tang, Qiuxiang; Lin, Tao (Frontiers in Plant Science, 2025)
IntroductionPolyethylene mulch film (PE) is a key agricultural practice for enhancing crop production and income in water-scarce regions. However, the complete recycling of PE remains challenging, resulting in the persistence of residual film fragments in the soil, which compromises soil structure and negatively impacts crop growth and yield potential. Although biodegradable mulch film (BEMF) is considered a promising alternative, the underlying mechanisms governing its regulation of soil water and thermal dynamics, as well as its subsequent impacts on crop productivity, are yet to be fully elucidated.MethodsTherefore, a comprehensive understanding of how BEMF influences soil water dynamics, thermal regimes, and crop growth and development is crucial for assessing its ecological adaptability. In this study field plot experiments were carried out over three consecutive growing seasons (2021 - 2023) under three irrigation quotas: W1 (63.6% crop evapotranspiration [ETc], 315 mm), W2 (81.8% ETc, 405 mm), and W3 (100% ETc, 495 mm).ResultsThis study systematically evaluated the impacts of PE and biodegradable mulch films (BEMF: B1 and B2) on soil hydrothermal dynamics, cotton photosynthetic productivity, and water use efficiency under varying irrigation quotas. Furthermore, the economic and ecological benefits of cotton fields under these treatments were analyzed. The findings revealed that PE left residual film fragments of 12.95 kg·ha-1 in the soil after mechanical recovery, while BEMF exhibited no such residue accumulation. However, BEMF reduced soil effective temperature by 100 - 111°C and soil water content (SWC) by 2.82 - 9.42% compared to PE. These adverse effects under BEMF significantly impaired cotton net photosynthetic rate (Pn) and photosynthetic product accumulation. Specifically, BEMF decreased cotton net Pn by 8.42 - 18.09%, photosynthetic product accumulation by 10.74 - 26.41%, and yield by 651 - 1079 kg·ha-1 relative to PE, particularly under the W1 irrigation level. Increasing the irrigation quota mitigated soil water and heat deficits, enhanced cotton net Pn and photosynthetic productivity, boosted yield by 1.76 - 31.72%, and increased economic income by 552 - 12,423 CNY·ha-1.DiscussionIn summary, this study provides a new ecological regional adaptation scheme for BEFM, highlighting that under conventional conditions, BEFM cannot fully substitute the yield advantages of PEFM. Nevertheless, the application of an additional 90 mm of irrigation water effectively mitigates the yield and economic losses associated with BEMF while eliminating the risk of residual film fragment accumulation in the soil. These findings offer valuable insights for advancing the green and sustainable management of agricultural ecosystems.